Effect of Aspiration on Vowel Duration for Voice and Voiceless Unaspirated (Garhwali Hindi) Consonants - S.K. Adhikari (BMC Journal of Scientific Research, 2018)
In this paper, an attempt has been made to study of Vowel durations for voice and voiceless unaspirated consonant. An experiment is described to study vowel duration of 10 vowels (Garhwali Hindi) with different unaspirated consonants. Ten Garhwali vowels word in /CVC/ syllables as spoken three times by ten males and ten females Garhwali speakers were recorded in system in the free field of partially acoustically treated room. SFS/PRRAT software is used to digitize and analyze the data. Linear predictive coding (LPC) spectra were obtained for each of vowels and vowel duration was measured. Then we found that vowel duration of voice unaspirated consonant is greater than voiceless unaspirated consonants.